Composite electrode material as well as pole piece and battery applying composite electrode material
By doping and coating metal elements of lithium iron phosphate and lithium iron manganese phosphate materials, the composite electrode materials were prepared, which solved the problems of poor energy density and circulation performance, achieved the improvement of high specific energy and circulation performance, and improved the Overall performance of the battery.
Patent Information
- Application Number
- CN202411411868.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
AI Technical Summary
Lithium iron phosphate and lithium iron phosphate manganese iron phosphate electrode materials have problems with low energy density and poor circulation performance in actual applications, resulting in limited application of their applications in batteries.
By doping and coating metal elements of lithium iron phosphate and lithium iron manganese phosphate materials, composite electrode materials are prepared to improve their energy density and conductivity, and to combine their high platform voltage and good cycling performance by blending modified materials Features.
It significantly improves the energy density and conductivity of lithium iron phosphate and lithium iron manganese phosphate, improves the dissolution of Mn ion, improves the circulation performance and safety stability of the battery, and provides a composite electrode material with high specific energy and both circulation performance. .
Smart Images

Figure BDA0005079634590000051 
Figure BDA0005079634590000071 
Figure BDA0005079634590000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of batteries, and in particular relates to a composite electrode material and an electrode sheet and a battery using the composite electrode material. Background Art
[0002] With the energy crisis, growing energy demand and emerging ecological problems, developing environmentally friendly, sustainable and renewable energy is one of the most severe challenges that mankind must face in the 21st century. In recent years, with the rapid development of new energy and electronic devices, energy conversion and storage has become an important issue that needs to be solved urgently, and batteries and capacitors are currently the commonly used energy storage methods. Among them, batteries have the advantages of high specific capacity and suitability for large-scale commercial production. Therefore, key materials for batteries have attracted much attention. As an indispensable part of batteries, electrode materials directly determine important properties of batteries such as electrochemical properties and safety performance.
[0003] Lithium iron phosphate (LiFePO4) and lithium iron manganese phosphate (LiMn x Fe (1-x) PO4) is one of the most popular electrode materials in the battery field. Although they all have similar material properties, such as high safety, good electrochemical performance and relatively low cost, they also have different limitations and challenges. Among them, for LiFePO4, there are problems such as low energy density and weak conductivity; for LiMn x Fe (1-x) PO4 has lower electronic conductivity and active Mn 3+ Therefore, whether it is LiFePO4 or LiMn x Fe (1-x) When PO4 is used in batteries, there will be problems with low energy density and poor cycle performance, which leads to certain limitations in the practical application of both. Summary of the invention
[0004] In order to improve the energy density and conductivity of lithium iron phosphate and lithium iron manganese phosphate, the present invention provides a composite electrode material and an electrode sheet and a battery using the same.
[0005] According to one aspect of the present invention, a composite electrode material is provided, which includes a modified lithium iron manganese phosphate material and a modified lithium iron phosphate material; wherein the modified lithium iron manganese phosphate material includes a core layer and a shell layer, the core layer includes a first metal element, the shell layer includes a second metal element, and the modified lithium iron manganese phosphate material is prepared by doping with an oxide of the first metal element and coating with an oxide of the second metal element; the modified lithium iron phosphate material includes a third metal element, and the modified lithium iron phosphate material is prepared by doping with an oxide of the third metal element.
[0006] The present invention modifies lithium iron phosphate and lithium iron manganese phosphate, realizes metal element doping of lithium iron phosphate and lithium iron manganese phosphate, and metal element coating of lithium iron manganese phosphate, which can improve the energy density and conductivity of lithium iron phosphate and lithium iron manganese phosphate, and improve the Mn ion dissolution problem. In addition, the present invention prepares a composite electrode material by mixing modified lithium iron manganese phosphate material and modified lithium iron phosphate material, which can combine the characteristics of high platform voltage of lithium iron manganese phosphate material and good cycle performance of lithium iron phosphate material, and provide a composite electrode material with high specific energy and good cycle performance for the battery field.
[0007] Preferably, the oxide of the first metal element includes at least one of titanium, zirconium and magnesium. When the lithium manganese iron phosphate is doped with the above metal elements, it is beneficial to improve the electronic structure of the lithium manganese iron phosphate and enhance the conductivity of the lithium manganese iron phosphate.
[0008] Preferably, in the modified lithium manganese iron phosphate material, the mass content of the first metal element is 1000-3500 ppm.
[0009] Preferably, the oxide of the second metal element includes at least one of niobium and calcium. When the lithium manganese iron phosphate is coated with the above metal elements, it is beneficial to further improve the dissolution of Mn ions in the lithium manganese iron phosphate, thereby improving the safety and stability of the battery using the lithium manganese iron phosphate.
[0010] Preferably, in the modified lithium manganese iron phosphate material, the mass content of the second metal element is 500-2000 ppm.
[0011] Preferably, the third metal element includes at least one of cobalt, vanadium and molybdenum. When lithium iron phosphate is doped with the above metal elements, it is beneficial to enhance the electrical properties of lithium iron phosphate, thereby improving the cycle performance of the battery using the lithium iron phosphate.
[0012] Preferably, in the modified lithium iron phosphate material, the mass content of the third metal element is 1000-3500 ppm.
[0013] Preferably, the particle size of the modified lithium manganese iron phosphate material is 0.5 to 2.5 μm, and / or the particle size of the modified lithium iron phosphate material is 0.5 to 2.5 μm.
[0014] Preferably, the particle size of the modified lithium iron phosphate material is 0.5 to 1 μm, and / or the particle size of the modified lithium iron phosphate material is 1 to 2.5 μm. When the modified lithium iron phosphate material is mixed with the modified lithium iron phosphate material, its particle size will affect the performance of the composite electrode material. When the modified lithium iron phosphate material and the modified lithium iron phosphate material are within the above particle size range, the composite electrode material can be guaranteed to have both excellent electrical properties and high compaction density.
[0015] Preferably, the particle size of the composite electrode material is 0.5-1 μm.
[0016] Preferably, the compaction density of the composite electrode material is 2.55 to 2.60 g / cm 3 .
[0017] Preferably, the core is prepared by doping lithium iron manganese phosphate with the oxide of the first metal element; and / or the modified lithium iron manganese phosphate material is prepared by coating the core with the oxide of the second metal element; and / or the modified lithium iron phosphate material is prepared by doping lithium iron phosphate with the oxide of the third metal element. The present invention uses metal oxides to modify lithium iron phosphate and lithium iron manganese phosphate, which can improve the crystal structure stability of the material in the doping process and the conductivity of the material in the coating process, thereby enhancing the electrical properties and cycle stability of the prepared modified lithium iron manganese phosphate material and modified lithium iron phosphate material.
[0018] Preferably, calculated by mass ratio, in the composite electrode material, the modified lithium manganese iron phosphate material: modified lithium iron phosphate material=1:(0.1-1).
[0019] Preferably, the method for preparing a modified lithium iron manganese phosphate material comprises the following steps: S1. mixing a manganese iron phosphate precursor, a lithium source, a phosphorus source, a carbon source and an oxide of a first metal element, and obtaining a first reactant by ball milling; S2. subjecting the first reactant to sand milling, spray drying and high-temperature calcination to obtain a second reactant; S3. mixing the second reactant with the oxide of a second metal element, and reacting them at 200 to 500° C. for 5 to 15 hours to obtain a modified lithium iron manganese phosphate material.
[0020] Preferably, the method for preparing modified lithium iron phosphate material comprises the following steps: step 1. mixing an iron source, a lithium source, a phosphorus source, a carbon source and an oxide of a third metal element and subjecting the mixture to ball milling to obtain reactant I; step 2. subjecting reactant I to sand milling, spray drying and high-temperature calcination to obtain modified lithium iron phosphate material.
[0021] Preferably, the iron source includes at least one of iron oxide, iron hydroxide, ferric phosphate and ferrous phosphate.
[0022] Preferably, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate and lithium phosphate.
[0023] Preferably, the phosphorus source includes at least one of phosphoric acid, lithium monohydrogen phosphate, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, and lithium phosphate.
[0024] Preferably, the carbon source includes at least one of glucose, sucrose, starch and phenolic resin.
[0025] Preferably, in S1, the amount of the iron manganese phosphate precursor is n1, and the amount of the lithium source is n2, wherein 0.98≤n2 / n1≤1.1.
[0026] Preferably, in S1, the amount of the iron manganese phosphate precursor source is n1, and the amount of the phosphorus source is n3, wherein 0.9≤n1 / n3≤1.0.
[0027] Preferably, in S1, the amount of carbon source added is 10% to 20% of n1.
[0028] Preferably, in S1, the added amount of the oxide of the first metal element is 1% to 2% of n1.
[0029] Preferably, in S3, the amount of the oxide of the second metal element added is 1% to 2% of n1.
[0030] Preferably,
[0031] Preferably, in step 1, the amount of the iron source substance is n4, and the amount of the lithium source substance is n5, wherein 0.98≤n5 / n4≤1.1.
[0032] Preferably, in step 1, the amount of the iron source is n4, and the amount of the phosphorus source is n6, wherein 0.9≤n4 / n6≤1.0.
[0033] Preferably, in step 1, the amount of carbon source added is 10% to 15% of n4.
[0034] Preferably, in step 1, the oxide of the third metal element is added in an amount of 1% to 2% of n1.
[0035] Preferably, the particle size of the first reactant after sand milling is 0.1-0.8 μm.
[0036] Preferably, the particle size of the reactant I after sand milling is 0.5-1.5 μm.
[0037] Preferably, the spray drying process is carried out under the reaction conditions of an inlet air temperature of 260±5°C and a feed rate of 50±5rpm.
[0038] Preferably, the first reactant is subjected to high temperature calcination treatment under the conditions of 600-800° C. for 6-12 hours in an inert gas atmosphere.
[0039] Preferably, the high temperature calcination treatment of the reactant I is carried out under an inert gas atmosphere at 600 to 1000° C. for 5 to 15 hours.
[0040] Preferably, the method for preparing the composite electrode material comprises the following steps: mixing the modified lithium manganese iron phosphate material with the modified lithium iron phosphate material, reacting them at 300-500° C. for 5-10 hours under an inert gas atmosphere to obtain the composite electrode material.
[0041] In a second aspect, the present invention provides a pole piece, which comprises the above-mentioned composite electrode material.
[0042] In a third aspect, the present invention provides a battery, comprising the above-mentioned electrode. DETAILED DESCRIPTION
[0043] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0044] Example 1
[0045] Treatment Group 1A
[0046] 1. Raw materials for preparing composite electrode materials
[0047] The raw materials for preparing the composite electrode material in treatment group 1A of this embodiment are shown in Table 1, and the raw materials are prepared according to Table 1.
[0048] Table 1. Raw materials used in treatment group 1A of this example
[0049]
[0050] 2. Preparation method of composite electrode materials
[0051] (1) Preparation of modified lithium manganese iron phosphate
[0052] S1. A manganese iron phosphate precursor, a lithium source, a phosphorus source, a carbon source and an oxide of a first metal element are mixed by ball milling for 1 hour to obtain a first reactant, wherein the amount of the manganese iron phosphate precursor is n1, the amount of the lithium source is n2, the amount of the phosphorus source is n3, n2 / n1=1.1, n1 / n3=0.95, the amount of the carbon source added is 10% of n1, and the amount of the oxide of the first metal element added is 1% of n1;
[0053] S2. The first reactant is subjected to sand grinding, spray drying, and high-temperature calcination in sequence to obtain a second reactant; wherein the sand grinding is performed by sand grinding for 2 hours using an inverted can method, and the particle size of the reactant is controlled to be 0.45 μn; the spray drying reaction conditions are carried out under the reaction conditions of an inlet air temperature of 260±5°C and a feed rate of 50±5 rpn; the high-temperature calcination reaction conditions are carried out under a nitrogen atmosphere at 650°C for 8 hours;
[0054] S3. The second reactant is mixed with the oxide of the second metal element, reacted at 300° C. for 10 hours, and then the obtained reactant is broken up by air flow crushing to obtain a modified lithium manganese iron phosphate material with a particle size of 0.5 μm, wherein the amount of the oxide of the second metal element added is 1% of n1.
[0055] (2) Preparation of modified lithium iron phosphate
[0056] Step 1. Mix an iron source, a lithium source, a phosphorus source, a carbon source and an oxide of a third metal element and obtain a reactant I by ball milling, wherein the amount of the iron source is n4, the amount of the lithium source is n5, the amount of the phosphorus source is n6, n5 / n4=1.1, n4 / n6=0.95, the amount of the carbon source added is 10% of n4, and the amount of the oxide of the third metal element added is 1% of n4;
[0057] Step 2. The reactant I is subjected to sand grinding, spray drying, and high-temperature calcination to obtain a modified lithium iron phosphate material; wherein the sand grinding is performed by sand grinding for 1 hour using an inverted can method, and the particle size of the reactant is controlled to be 0.8 μm; the reaction conditions for the spray drying are carried out under the reaction conditions of an inlet air temperature of 260±5°C and a feed rate of 50±5rpm; the reaction conditions for the high-temperature calcination are reacted at 800°C for 10 hours under a nitrogen atmosphere, and then the obtained reactant is broken up by air flow crushing to obtain a modified lithium iron phosphate material with a particle size of 1.5 μm.
[0058] (3) Preparation of composite electrode materials
[0059] The modified lithium iron phosphate material and the modified lithium iron phosphate material were mixed at a mass ratio of modified lithium iron phosphate material: modified lithium iron phosphate material = 1:0.1, and the mixture was reacted at 300° C. for 10 hours under an inert gas atmosphere to obtain a composite electrode material with a particle size of 1.0 μm.
[0060] 3. Preparation of Cells
[0061] The prepared composite electrode material, binder (PVDF) and conductive agent (SP) were mixed in a mass ratio of composite electrode material: binder: conductive agent = 80:15:5 to prepare a positive electrode. A lithium sheet was used as a negative electrode, PP was used as a separator, and LiPF6 was used as an electrolyte to assemble with the prepared positive electrode to prepare a battery.
[0062] The treatment groups 2A to 7A and the comparison group 1A of Example 1 prepare the composite electrode material with reference to the formula and method provided by the treatment group 1A of Example 1, with the material and input amount of the oxide of the first metal element used in the modified lithium manganese iron phosphate material in the formula (adjusted based on n1 as a benchmark) as variables. The variables used by the treatment groups 2A to 7A and the comparison group 1A of Example 1 to prepare the modified lithium manganese iron phosphate material are shown in Table 2. Except for the above differences, the operating steps for preparing the modified lithium manganese iron phosphate material, the modified lithium iron phosphate material, the composite electrode material, the pole piece and the battery by the treatment groups 2A to 7A and the comparison group 1A of Example 1 are strictly consistent with those of the treatment group 1A of Example 1.
[0063] Table 2. Variables of each treatment group and control group in Example 1
[0064]
[0065] Comparative Group 2A
[0066] This comparative group prepares modified lithium iron manganese phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery with reference to the formula and method provided by treatment group 1A of Example 1. The difference from treatment group 1A of Example 1 is that the first metal element oxide is not added when preparing the modified lithium iron manganese phosphate material. In addition to the above differences, the operation steps of preparing modified lithium iron manganese phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery in this comparative group are strictly consistent with those of treatment group 1A of Example 1.
[0067] Comparative group 3A
[0068] This comparative group prepares modified lithium iron manganese phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery with reference to the formula and method provided by treatment group 1A of Example 1. The difference from treatment group 1A of Example 1 is that the second metal element oxide is not added when preparing the modified lithium iron manganese phosphate material. In addition to the above differences, the operation steps of preparing modified lithium iron manganese phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery in this comparative group are strictly consistent with those of treatment group 1A of Example 1.
[0069] Comparative group 4A
[0070] This comparative group prepares modified lithium iron phosphate materials, composite electrode materials, pole pieces and batteries with reference to the formula and method provided by treatment group 1A of Example 1. The difference from treatment group 1A of Example 1 is that when preparing the composite electrode material, this comparative group replaces the modified lithium iron manganese phosphate material provided by the present invention with an equal mass fraction of commercial lithium iron manganese phosphate material (not modified by metal element oxide). Except for the above differences, the operation steps of preparing modified lithium iron manganese phosphate materials, modified lithium iron phosphate materials, composite electrode materials, pole pieces and batteries in this comparative group are strictly consistent with those of treatment group 1A of Example 1.
[0071] Test Example 1
[0072] 1. Test subjects
[0073] Batteries prepared in each treatment group and comparison group of Example 1.
[0074] 2. Test Method
[0075] (1) Capacity retention rate: The test object is charged and discharged at 0.2C for one cycle at room temperature (25°C), and then cycled at 1C for 100 cycles. The capacity retention rate is calculated using the following formula:
[0076] (Discharge capacity at 100 cycles / discharge capacity at the first cycle of 1C cycle)*100%.
[0077] (2) Discharge capacity: The test object was charged and discharged at a rate of 0.1C at a room temperature of 25°C, with a cut-off voltage of 2.0 to 4.25V and a cut-off current of 0.05C.
[0078] (3) Metal element content: The specific method is to be tested in accordance with the contents in Appendix C of GB / T33822-2017 "Nano lithium iron phosphate";
[0079] (4) Mn dissolution: The specific method is tested in accordance with the contents of GB / T 33822-2017 "Nano-lithium iron phosphate".
[0080] 3. Test results and analysis
[0081] The test results of this test example are shown in Table 3. Among them, different metal oxides are used to dope the lithium iron manganese phosphate material in treatment groups 1A to 4A and comparison group 1A. It can be seen from the test data that when the oxide of the first metal element is selected from at least one of titanium oxide, zirconium oxide, and magnesium oxide, it is beneficial to improve the electronic structure of lithium iron manganese phosphate, adjust the conductivity of lithium iron manganese phosphate, and improve the cycle performance and discharge capacity of the battery using it. When metal hydroxide is used for doping instead of metal oxide, as shown in treatment group 5A, the cycle performance of the battery using the modified lithium iron manganese phosphate material decreases. In addition, combined with comparison groups 2A to 4A, it can be seen that metal element doping and metal element coating of lithium iron manganese phosphate can significantly improve the conductivity of lithium iron manganese phosphate and improve the problem of Mn ion dissolution in lithium iron manganese phosphate.
[0082] In addition, in treatment group 1A and treatment groups 6A to 8A, it can be found through testing that in the modified lithium manganese iron phosphate material, when the content of the first metal element meets 1000 to 3500 ppm, it has a better discharge capacity.
[0083] Table 3. Test results of test case 1
[0084]
[0085] Example 2
[0086] Treatment group 1B of Example 2 is strictly in accordance with the formula and method provided by treatment group 1A of Example 1 to prepare modified lithium manganese iron phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery.
[0087] The treatment groups 2B to 7B of Example 2 and the comparison group 1B prepare the composite electrode material with reference to the formula and method provided by the treatment group 1B of Example 2, with the material and input amount of the oxide of the second metal element used in the modified lithium manganese iron phosphate material in the formula (adjusted based on n1 as a benchmark) as variables. The variables used to prepare the modified lithium manganese iron phosphate material in the treatment groups 2B to 7B of Example 2 and the comparison group 1B are shown in Table 4. Except for the above differences, the operating steps for preparing the modified lithium manganese iron phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery in the treatment groups 2B to 7B of Example 2 and the comparison group 1B are strictly consistent with those of the treatment group 1B of Example 2.
[0088] Table 4. Variables of each treatment group and control group in Example 2
[0089]
[0090]
[0091] Comparative group 2B
[0092] This comparative group strictly follows the formula and method provided in comparative group 2A of Example 1 to prepare modified lithium manganese iron phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery.
[0093] Comparative group 3B
[0094] This comparative group strictly follows the formula and method provided in comparative group 3A of Example 1 to prepare modified lithium manganese iron phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery.
[0095] Comparative group 4B
[0096] This comparative group strictly follows the formula and method provided in comparative group 4A of Example 1 to prepare modified lithium manganese iron phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery.
[0097] Test Example 2
[0098] 1. Test subjects
[0099] Batteries prepared in each treatment group and comparison group of Example 2.
[0100] 2. Test Method
[0101] Refer to the test method provided in Test Example 1.
[0102] 3. Test results and analysis
[0103] The test results of this test example are shown in Table 5. Among them, different metal oxides are used to coat the lithium iron manganese phosphate material in treatment groups 1B to 3B and comparison group 1B. It can be seen from the test data that when the oxide of the second metal element is selected from at least one of niobium oxide and calcium oxide, it is beneficial to further improve the dissolution of Mn ions in the lithium iron manganese phosphate, thereby improving the safety and stability of the battery using it. When metal hydroxide is used for coating instead of metal oxide, as shown in treatment group 4B, the Mn dissolution content of the battery using the modified lithium iron manganese phosphate material is improved. In addition, combined with comparison groups 2B to 4B, it can be seen that metal element doping and metal element coating of lithium iron manganese phosphate can significantly improve the conductivity of lithium iron manganese phosphate and improve the problem of Mn ion dissolution in lithium iron manganese phosphate.
[0104] In addition, in treatment group 1B and treatment groups 5B to 7B, it can be found through testing that in the modified lithium manganese iron phosphate material, when the content of the second metal element meets 500 to 2000 ppm, it has better cycle performance.
[0105] Table 5. Test results of test case 2
[0106]
[0107] Example 3
[0108] Treatment group 1C of Example 3 is strictly in accordance with the formula and method provided by treatment group 1A of Example 1 to prepare modified lithium manganese iron phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery.
[0109] Treatment groups 2C to 8C of Example 3 prepare composite electrode materials with reference to the formula and method provided by treatment group 1C of Example 3, with the mass ratio of modified lithium iron phosphate material to modified lithium iron manganese phosphate material in the formula and the particle size of the two as variables (the particle size is adjusted by controlling the size of sand milling and air flow crushing in the preparation of modified lithium iron phosphate material and modified lithium iron manganese phosphate material). The variables used to prepare modified lithium iron phosphate materials in treatment groups 1C to 8C of Example 3 are shown in Table 6. Except for the above differences, the operating steps of treatment groups 1C to 8C of Example 3 for preparing modified lithium iron manganese phosphate materials, modified lithium iron phosphate materials, composite electrode materials, pole pieces and batteries are strictly consistent with those of treatment group 1C of Example 3.
[0110] Table 6. Variables of each treatment group and control group in Example 3
[0111]
[0112]
[0113] Comparative group 1C
[0114] This comparative group strictly follows the formula and method provided in comparative group 2A of Example 1 to prepare modified lithium manganese iron phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery.
[0115] Comparative group 2C
[0116] This comparative group strictly follows the formula and method provided in comparative group 3A of Example 1 to prepare modified lithium manganese iron phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery.
[0117] Comparative group 3C
[0118] This comparative group strictly follows the formula and method provided in comparative group 4A of Example 1 to prepare modified lithium manganese iron phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery.
[0119] Comparative group 4C
[0120] This comparative group prepares modified lithium iron manganese phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery with reference to the formula and method provided by treatment group 1C of Example 3. The difference from treatment group 1C of Example 3 is that this comparative group does not add oxide of the third metal element when preparing the modified lithium iron phosphate material. In addition to the above differences, the operation steps of preparing modified lithium iron manganese phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery in this comparative group are strictly consistent with those of treatment group 1C of Example 3.
[0121] Comparative group 5C
[0122] This comparative group prepares modified lithium iron manganese phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery with reference to the formula and method provided by treatment group 1C of Example 3. The difference from treatment group 1C of Example 3 is that when preparing the composite electrode material, this comparative group replaces the modified lithium iron manganese phosphate material provided by the present invention with an equal mass fraction of commercial lithium iron manganese phosphate material (not modified by metal oxide), and replaces the modified lithium iron phosphate material provided by the present invention with an equal mass fraction of commercial lithium iron phosphate material (not modified by metal oxide). In addition to the above differences, the operation steps of preparing modified lithium iron manganese phosphate material, modified lithium iron phosphate material, composite electrode material, pole piece and battery in this comparative group are strictly consistent with those of treatment group 1C of Example 3.
[0123] Test Example 3
[0124] 1. Test subjects
[0125] Batteries prepared in each treatment group and comparison group of Example 3.
[0126] 2. Test Method
[0127] The tests of cycle performance, discharge capacity and Mn dissolution content refer to the test method provided in Test Example 1.
[0128] Compacted density: After applying a certain force to the sample and then releasing the force, the compacted sample thickness is measured and then the compacted density of the sample is obtained based on the weight of the sample. The reference document is the test method for powder compaction density in Appendix L of GB / T 24533-2019 "Graphite Anode Materials for Lithium-ion Batteries".
[0129] 3. Test results and analysis
[0130] The test results of this test example are shown in Table 7. Among them, in the treatment groups 1C to 5C, by changing the mass ratio between the modified lithium iron manganese phosphate material and the modified lithium iron phosphate material when preparing the composite electrode material, it can be confirmed through the data that with the increase of the modified lithium iron phosphate material in the composite electrode material, the cycle performance and discharge capacity of the battery using it show a trend of first increasing and then decreasing. Moreover, according to the mass ratio calculation, when the mass ratio of the modified lithium iron manganese phosphate material to the modified lithium iron phosphate material meets 1: (0.1~1), it has better cycle performance and discharge capacity. It can be explained that the present invention can provide a composite electrode material with high specific energy and cycle performance by blending the modified lithium iron manganese phosphate material and the lithium iron phosphate material in different proportions, combining the characteristics of high platform voltage of lithium iron manganese phosphate material and good cycle performance of lithium iron phosphate material.
[0131] Combined with comparison groups 1C to 5C, it can be illustrated that the composite electrode material provided by the present invention, compared with the single doping, single coating, and the same metal element doping or coating in the prior art, can significantly improve the electrical properties and cycle performance of the composite material by doping or coating with different metal oxides during the synthesis process of the modified lithium manganese iron phosphate material and the modified lithium iron phosphate material.
[0132] Furthermore, by analyzing the data provided by treatment group 1C and treatment groups 6C to 8C, it can be seen that by changing the particle size of the modified lithium iron manganese phosphate material and the modified lithium iron phosphate material, the electrical properties and compaction density of the composite electrode material will be affected, thereby affecting the cycle performance and discharge capacity of the battery using it. Further, it can be found from the data that when the particle size of the modified lithium iron manganese phosphate material is 0.5 to 1 μm, and / or the particle size of the modified lithium iron phosphate material is 1 to 2.5 μm, the compaction density of the composite electrode material obtained by using the above particle size range will be further improved, thereby making the battery using it have a higher discharge capacity.
[0133] Table 7. Test results of test case 3
[0134] Group Cycle performance / % Discharge capacity / (mAh / g) Mn dissolution content Compacted density Treatment Group 1C 98 161.2 15 2.56 Treatment Group 2C 99 160.8 10 2.60 Treatment Group 3C 98 161.3 14 2.55 Treatment Group 4C 97 159.2 20 2.50 Treatment Group 5C 98 155.5 12 2.52 Treatment Group 6C 98 161.0 13 2.55 Treatment Group 7C 96 152.7 27 2.51 Treatment Group 8C 96 152.8 29 2.53 Comparative group 1C 95 150.2 291 2.47 Comparative group 2C 95 152.5 224 2.45 Comparative group 3C 90 130 663 2.21 Comparative group 4C 90 150.3 26 2.48 Comparative group 5C 72 98 1328 2.01
[0135] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A composite electrode material, characterized in that: The composite electrode material includes modified lithium manganese iron phosphate material and modified lithium iron phosphate material; The modified lithium manganese iron phosphate material comprises a core and a coating layer, wherein the core is a lithium manganese iron phosphate material doped with a first metal element, and the coating layer comprises a second metal element; The modified lithium iron phosphate material includes a lithium iron phosphate material doped with a third metal element. The first metal element, the second metal element, and the third metal element are independently selected from one or more of titanium, zirconium, magnesium, calcium, cobalt, niobium, vanadium, and molybdenum.
2. The composite electrode material according to claim 1, characterized in that: The first metal element includes at least one of titanium, zirconium and magnesium.
3. The composite electrode material according to claim 2, characterized in that: In the modified lithium manganese iron phosphate material, the mass content of the first metal element is 1000 to 3500 ppm.
4. The composite electrode material according to claim 1, characterized in that The second metal element includes at least one of niobium and calcium.
5. The composite electrode material according to claim 4, characterized in that: In the modified lithium manganese iron phosphate material, the mass content of the second metal element is 500 to 2000 ppm.
6. The composite electrode material according to claim 1, characterized in that: The third metal element includes at least one of cobalt, vanadium and molybdenum.
7. The composite electrode material according to claim 6, characterized in that: In the modified lithium iron phosphate material, the mass content of the third metal element is 1000 to 3500 ppm.
8. The composite electrode material according to claim 1, characterized in that: The particle size of the modified lithium manganese iron phosphate material is 0.5 to 2.5 μm, and / or the particle size of the modified lithium iron phosphate material is 0.5 to 2.5 μm.
9. The composite electrode material according to claim 8, characterized in that: The particle size of the modified lithium manganese iron phosphate material is 0.5-1 μm, and / or the particle size of the modified lithium iron phosphate material is 1-2.5 μm.
10. The composite electrode material according to claim 1, characterized in that: The core is prepared by doping lithium manganese iron phosphate with the oxide of the first metal element; And / or, the modified lithium manganese iron phosphate material is prepared by coating the inner core with an oxide of the second metal element; And / or, the modified lithium iron phosphate material is prepared by doping lithium iron phosphate with the oxide of the third metal element.
11. The composite electrode material according to any one of claims 1 to 10, characterized in that: Calculated by mass ratio, in the composite electrode material, the modified lithium manganese iron phosphate material: the modified lithium iron phosphate material=1:(0.1-1).
12. A pole piece, characterized in that: The electrode sheet comprises the composite electrode material as claimed in any one of claims 1 to 11.
13. A battery, characterized in that: The battery comprises the electrode piece as claimed in claim 12.